GENOTYPE X ENVIRONMENT INTERACTION EFFECTS ON THE FIELD PERFORMANCE OF STEM AMARANTH (Amaranthus tricolor L.) (Bangladesh Journal of Plant Breeding and Genetics, 2017)
A research was carried out to find genotype x environment interaction effects on the field performance of 20 germplasm of Stem amaranth at Genetics Farm, Sher-e-Bangla Agricultural University, Dhaka during the period from November, 2013 to May 2014. The experiment was laid out in the Randomized Complete Block Design with three replications. Data were recorded on  plant height (cm), no. of leaves per plant, individual leaf weight (gm), individual stem weight (gm), marketable stem weight (gm), yield (Kg/ha) at three environments. G-18 was the tallest with non significant S2di value (10.5) and G-9 was the shortest (2.22). G-20 produced most number of leaves with non significant S2di value (2.59) and G-01 was the least (11.56**). G-01 was the highest individual leaf weight with significant S2di value (46.08**) and G-15 was the least (2.84). G-01 was the highest individual stem weight with non significant S2di value (15.13) and G-09 was the least (48.09). The genotype G-01 produced the highest marketable stem weight with non significant S2di value (451.59) and G-09 was the least (39.77). G-01 was the highest yield producing with non significant S2di value (7821.539) and G-09 was the least (688.8164). Based on stable responses considering the higher yield character G-08 and G-18, for higher individual leaf weight G-07 and G-11, for higher individual stem weight G-18, for lesser dry weight of stem G-14 and G-18 genotypes could be selected for effective use in breeding program.